2001
DOI: 10.1039/b107730a
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The activation energy for hydrogen abstraction from imidazolium-based ionic liquids is significantly higher than that observed in conventional solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 11 publications
(14 reference statements)
3
27
1
1
Order By: Relevance
“…The spectra in Bmim-TFSA are consistent with the spectrum recently measured in Bmim-PF 6 by Nishiyama et al 38 Therefore, as previously suggested, 18,19 hydrogen abstraction is slow in TMPA-TFSA.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The spectra in Bmim-TFSA are consistent with the spectrum recently measured in Bmim-PF 6 by Nishiyama et al 38 Therefore, as previously suggested, 18,19 hydrogen abstraction is slow in TMPA-TFSA.…”
Section: Resultssupporting
confidence: 90%
“…However, studies of the reaction of BP(T 1 ) in ILs are limited. 18,19,38 In TMPA-TFSA, the lifetime of BP(T 1 ) is reported to be 19 μs, which is substantially longer than the lifetimes in cyclohexane (300 ns), 2-propanol (5 ns), and benzene (3 μs). 19 In contrast, the lifetime of BP(T 1 ) in Bmim-TFSA has been reported to be 3 μs.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations